2012
DOI: 10.3747/pdi.2011.00092
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole-Imidazole Polyamide Targeting Transforming Growth Factor β1 Ameliorates Encapsulating Peritoneal Sclerosis

Abstract: ♦ Objective: Encapsulating peritoneal sclerosis (EPS) is a devastating fibrotic complication in patients treated with peritoneal dialysis (PD). Transforming growth factor β1 (TGF-β1) is a pivotal factor in the induction of EPS. ♦ Methods: To develop pyrrole-imidazole (PI) polyamide, a novel gene silencer, targeted to the TGF-β1 promoter (Polyamide) for EPS, we examined the effects of Polyamide on messenger RNA (mRNA) expression of TGF-β1, vascular endothelial growth factor (VEGF), and extracellular matrix (ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…We showed significant inhibition in human cells of TGF-β1 promoter activity and the expression of TGF-β1 mRNA and protein by PI polyamides, targeting the human TGF-β1 promoter [10]. We further showed that a PI polyamide targeting TGF-β1 could effectively retard the progression of renal diseases [11,12], post-angioplasty carotid artery stenosis [13], cornea fibrosis by alkali burns [14], skin hypertrophic scars [15], liver fibrosis [16], and encapsulating peritoneal sclerosis [17] in rats.…”
Section: Introductionmentioning
confidence: 90%
“…We showed significant inhibition in human cells of TGF-β1 promoter activity and the expression of TGF-β1 mRNA and protein by PI polyamides, targeting the human TGF-β1 promoter [10]. We further showed that a PI polyamide targeting TGF-β1 could effectively retard the progression of renal diseases [11,12], post-angioplasty carotid artery stenosis [13], cornea fibrosis by alkali burns [14], skin hypertrophic scars [15], liver fibrosis [16], and encapsulating peritoneal sclerosis [17] in rats.…”
Section: Introductionmentioning
confidence: 90%
“…Nevertheless, the binding of PI polyamide was reported to alter the conformation of double-stranded DNA promoter construction and impair target promoter activity [ 19 ]. We also reported that PI polyamides targeting the TGF-β1 promoter improved TGF-β1-induced fibrotic diseases such as progressive renal diseases [ 20 ], diabetic nephropathy [ 21 ], hypertrophic scar in marmoset [ 15 ], restenosis of arteries after injury [ 22 ], encapsulating peritoneal sclerosis [ 23 ], and suppressed dimethylnitrosamine-induced liver fibrosis [ 24 ]. In addition, pyridine derivative that inhibits TGF-β production improve HCV-related fibrosis and inflammation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not confirm inhibition of cancer progression via TGF-β1 suppression by GB1101 in protein level. However, we previously reported the GB1101 effects on various types of diseases such as nephropathy [ 20 ], hypertrophic scar [ 15 ], restenosis of arteries after injury [ 22 ], peritoneal sclerosis [ 23 ], and liver fibrosis [ 24 ] using rat or marmoset models. Therefore, the perspective of this study is to evaluate whether GB1101 would actually be available to cancer therapy by in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…This is an advantage of PI polyamides because as gene-silencers, side effects are reduced in comparison to nucleic acid medicines such as siRNA and antisense oligonucleotides, which knock down the target gene. We have demonstrated that PI polyamides targeting TGF-β1 promoter effectively ameliorate TGF-β1-induced diseases such as progressive renal diseases [ 9 ], restenosis of arteries after injury [ 10 ], and encapsulating peritoneal sclerosis [ 15 ]. However, the PI polyamides have not yet been developed into practical medicines for clinical use.…”
Section: Discussionmentioning
confidence: 99%